Factors influencing clothing interest of hijab among Muslim women in Klang Valley / Norhanim Syafuddin Tan - Syafuddin Tan, Norhanim (Faculty of Business and Management, 2020)
Hijab is considered as compulsory clothing apparels for Muslim women around the world. In Malaysia, the image of hijab and its wearer has shifted from an old fashioned look to modern and fashionable style. However, few past studies has found that fashion in hijab has overcome its main purpose which is to cover parts of Muslim woman body. As a result from this phenomenon, a study has been conducted to dig deeper what indicated Muslim women interest towards hijab as fashion apparels. The objectives to conduct this study is to identify the relationship between independent variable of self-concept, brand image, word-of-mouth and perceived quality towards clothing interest of hijab among Muslim woman in Klang Valley. In other words, researcher wants to study what factors induce Muslim woman attraction towards hijab as fashion items. The survey instrument was distributed through online platform to target sampling which is Muslim woman who wore hijab only. Researcher received 263 response but only 250 answered are valid. The data collected has been analyzed through SPSS 22.0 version in order to get reliability analysis, frequency analysis, descriptive analysis and multiple regression analysis. The result finding has determined the relationship between independent variables and dependent variables in this study. Therefore, recommendation and conclusion has been made for future researcher, practitioner, government and other parties.